Korelasi Minat Belajar dengan Hasil Belajar Akidah Akhlak Siswa Kelas X di MAN 4 Jombang - Aulia Masruroh; Sholihul Anshori (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Interest in lealrning with the sulbject of morall beliefs in MAlN 4 Jombalng is still less thaln theoreticall ulnderstalnding, stuldents malster pralctice in reall life alnd talke the malteriall for gralnted so thalt it hals aln impalct on stuldent lealrning oultcomes. So edulcaltors mulst alroulse alnd increalse the stuldents' interest in lealrning. The objectives of the stuldy were: 1) Lealrning Interest of Clalss X Stuldents in MAlN 4 Jombalng, 2) Lealrning Oultcomes of Morall Beliefs of Clalss X Stuldents in MAlN 4 Jombalng, 3) Correlaltion of Lealrning Interest with Lealrning Oultcomes of Clalss X Stuldents in MAlN 4 Jombalng. This stuldy ulses al qulalntitaltive resealrch methodology with al type of ex post falcto alpproalch thalt is correlaltionall. The salmple of this stuldy ulses al ralndom salmpling techniqule. Qulestionnalire daltal collection, tests alnd doculmentaltion. The resullts of this resealrch obtalined: 1) Very high Lealrning Interest 43 stuldents or 53%, high 33 stuldents or 41%, mediulm 5 stuldents or 6%, low 0 stuldents or 0%, very low 0 stuldents or 0% stalted thalt the culltivaltion of interest . 2) The lealrning oultcomes of 81 respondents hald al minimulm score of 16, aln alveralge score of 71, alnd al malximulm score of 88. In alddition, the stalndalrd devialtion vallule is 17.03852. 3) There is al positive alnd significalnt correlaltion between lealrning interest alnd the lealrning oultcomes of stuldents of clalss X morall beliefs in MAlN 4 Jombalng.